TGI Fridays In Kandahar: Fast Food, Military Contracting, and Intimacies of Force in the Iraq and Afghanistan Wars (Journal of Transnational American Studies)
During the height of the US wars in Iraq and Afghanistan from 2004 to 2014, US military bases featured an amenity both familiar and unexpected: name-brand fast food (NBFF), such as TGI Friday’s, Burger King, Subway, and Pizza Hut. Drawing on firsthand accounts from soldiers, journalists, and bloggers, as well as academic literatures on critical food studies and cultures of imperialism, this article analyzes the circulation of NBFF in Iraq and Afghanistan as a mechanism by which to sustain US imperialism. It argues that NBFF generates the intimacy of “home” for US soldier-consumers and is deployed as enticing inducement for an all-volunteer military force to perform the necessary labor to maintain US empire across two war zones. NBFF simultaneously provided a profitable opportunity for the expansion of US corporations and capital, as contractors and subcontractors from across the global supply chain were mobilized to provide easy access to these comfort foods. Thus, the article traces the ways in which the chemosensory experience of consumption has served as a way of inducing some bodies to serve—to maim and kill other bodies—while requiring still other bodies to serve in mobilizing and facilitating the logistics of these encounters.